Star Formation in Galaxy Evolution: Connecting Numerical Models to Reality: Saas-Fee Advanced Course 43. Swiss Society for Astrophysics and Astronomy - Gnedin, Nickolay Y.; Glover, Simon; Klessen, Ralf S.; Springel, Volker (Springer, 2016)
Physical Processes in the Interstellar Medium -- High performance computing and numerical modelling -- Index.
Keywords: Konferenzschrift -- 2013 -- Villars-sur-Ollon; Sternentstehung